2017
DOI: 10.1093/mnras/stx1743
|View full text |Cite
|
Sign up to set email alerts
|

VLBA 24 and 43 GHz observations of massive binary black hole candidate PKS 1155 + 251

Abstract: PKS 1155+251 is a radio-loud quasar source at z = 0.203. Observations using very long baseline interferometry (VLBI) at ∼2, 5, 8 and 15 GHz show that the structure of the radio source is quite complicated on parsec scales and that the outer hot spots are apparently undergoing a significant contraction. Because these results cannot be fully explained based on the compact symmetric object (CSO) scenario with a radio core located between the northern and southern complexes, we made observations with the Very Long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In PKS1155+251, the components appear to be moving inwards resulting in the source shrinking in size (Tremblay et al, 2008). Yang et al (2017) observed the source with the VLBA at 24 and 43 GHz and suggested that the southern component may harbour another black hole. Further observations are required to clarify the nature of this source.…”
Section: Proper Motionmentioning
confidence: 99%
“…In PKS1155+251, the components appear to be moving inwards resulting in the source shrinking in size (Tremblay et al, 2008). Yang et al (2017) observed the source with the VLBA at 24 and 43 GHz and suggested that the southern component may harbour another black hole. Further observations are required to clarify the nature of this source.…”
Section: Proper Motionmentioning
confidence: 99%
“…Such an extension is unusual but not unprecedented among CSOs. For example, the quasar PKS 1155+251 (Yang et al 2017) shows a similar feature, where the steep-spectrum trail emission extends to a distance of ∼ 90 pc. A possible explanation is the brightening of the hot spot in a transverse direction within the lobe due to pressure differences at the location of the jet-ISM interaction.…”
Section: Eastern Extensionmentioning
confidence: 96%
“…Temporal variability, double-peaked emission lines, and helical jet structures have all been used to identify BBH candidates. Direct imaging of parsec-or subparsec-scale separated BBHs has been carried out by Very Long Baseline Interferometry (VLBI) techniques (e.g., Rodriguez et al 2006;Deane et al 2014;Kharb et al 2017;Yang et al 2017;Kharb et al 2020). Multiple direct and indirect observational techniques throughout the whole electromagnetic spectrum have been used to confirm two supermassive black holes (SMBHs) in any given binary system (see De Rosa et al 2019 for a review).…”
Section: Introductionmentioning
confidence: 99%